Proteome‐wide analysis of T‐cell response to BK polyomavirus in healthy virus carriers and kidney transplant recipients reveals a unique transcriptional and functional profile. Issue 1 (14th January 2020) - Ambalathingal, George R; Francis, Ross S; Corvino, Dillon; Srihari, Sriganesh; Aftab, Blake T; Smith, Corey; Khanna, Rajiv
Abstract: Objectives: Cellular immunity against BK polyomavirus (BKV)‐encoded antigens plays a crucial role in long‐term protection against virus‐associated pathogenesis in transplant recipients. However, in‐depth understanding on dynamics of these cellular immune responses is required to develop better immune monitoring and immunotherapeutic strategies. Methods: Here, we have conducted a proteome‐wide analysis of BKV‐specific T‐cell responses in a cohort of 53 healthy individuals and 26 kidney transplant recipients to delineate the functional and transcriptional profile of these effector cells and compared these characteristics to T cells directed against cytomegalovirus, which is also known to cause significant morbidity in transplant recipients. Results: Profiling of BKV‐specific CD4 + and CD8 + T cells revealed that kidney transplant recipients with high levels of circulating viraemia showed significantly reduced T‐cell reactivity against large T and/or small T antigens when compared to healthy donors. Interestingly, T cells specific for these antigens showed strong cross‐recognition to orthologous JC virus (JCV) peptides, including those exhibiting varying degrees of sequence identity. Ex vivo functional and phenotypic characterisation revealed that the majority of BKV‐specific T cells from renal transplant recipients expressed low levels of the key transcriptional regulators T‐bet and eomesodermin, which was coincident with undetectable expression of granzyme B and perforin. However, in vitro stimulation of T cells with BKV epitopes selectively enhanced the expression of T‐bet, granzyme B and cellular trafficking molecules (CCR4, CD49d and CD103) with minimal change in eomesodermin and perforin. Conclusions: These observations provide an important platform for the future development of immune monitoring and adoptive T‐cell therapy strategies for BKV‐associated diseases in transplant recipients, which may also be exploited for similar therapeutic value in JCV‐associated clinical complications. Abstract : This manuscript provides comprehensive profiling of BK polyomavirus T‐cell responses in healthy virus carriers and kidney transplant recipients.